Silagens de cereais de inverno: variabilidade inter e intraespecífica quanto ao rendimento e valor nutritivo - Lehmen, Rosilene Inês (2013)
In Southern Brazil, the autumn season is characterized for lower forage offer, as well as low nutritive value, which hamper the adequate animal nutrition and result in body weight losses and milk yield reduction. Winter cereals used as silage, could be an alternative for fluctuation yield reduction. However, is necessary to know and select adequate genotypes for ensilage, base on quantity and nutritive value, meaning biomass yield and animal product. The objective this work was select winter cereals genotypes by biomass yield, nutritive value and fermentative parameters of silage evaluations. Were evaluated winter annual grasses genotypes (white oat, wheat, triticale, rye, barley and black oat). The genotypes were ensiled at dough grain to firm mass stages, with 30 at 35% dry matter, and packaged in PVC experimental silos. The design was randomized complete block , with three replications and forty genotypes. Were determined the biomass yield for ensilage, dry matter concentration, nutritive value and fermentative parameters for silage. All genotypes evaluated present satisfactory characteristics for ensilage. The BRS Serrano rye presented greater biomass yield. The BRS Cauê barley, BRS Umbu wheat and UFRGS 19, URS Fapa-Slava and UPF 16 white oats present higher crude protein concentrations